Distribution and Pattern of Dengue Fever Cases in Bandung City, 2023, Indonesia: A Spatial Analysis Approach - Yohana Allyn Setyawati; Adi Anggoro Parulian; Yura Witsqa Firmansyah (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Dengue haemorrhagic fever (DHF) is a significant health concern, categorised as a neglected tropical disease that requires substantial attention due to its high Case Fatality Rate (CFR) and associated mortality, especially in outbreak situations. DHF results from the dengue virus, categorised within group B of Arthropod-Borne Viruses (Arboviruses). The Bandung City Health Office reported 5,205 cases of dengue haemorrhagic fever in 2022 consisting of 2,646 (51%) male and 2,559 (49%) female patients. This study employs spatial analysis to chart the distribution of DHF cases, allowing for an assessment of potential spatial autocorrelation of DHF within the Bandung City region. This study on autocorrelation employed a retrospective cohort research design. This study focused on the incidence rates of DHF as reported by the Bandung City Health Office, with the analysis encompassing 30 sub-districts within Bandung City. The technique employed for sampling was total sampling. The independent variable in this investigation is the occurrence of DHF. The Moran I Index was employed in the spatial analysis to examine the distribution pattern of the variable. DHF incidence in 30 sub-districts of Bandung City is clustered with a Moran index value of 0.120934 in the interval 0 ≤ I ≤ 1, indicating positive spatial autocorrelation. The p-value of 0.001585 is smaller than the α value (5%), indicating statistical significance. The spatial pattern of DHF incidence is clustered, and there is autocorrelation between sub-districts in Bandung City in 2023. The distribution of DHF cases in Bandung City in 2023 is clustered. Scientific studies in the form of spatial analyses are recommended to be conducted in DHF endemic areas on a regular basis because they can provide basic information to support effective prevention and control of DHF cases.